Proses Hidrolisis dan Fermentasi Tandan Kosong Kelapa Sawit sebagai Bahan Baku Bioetanol - Endang Purnama Sari; Putri Azurah Fani; Abubakar Abubakar; Mukhlishien Mukhlishien (Universitas Syiah Kuala, 2020)
Bioethanol can be used as an environmentally friendly alternative fuel and is produced from renewable raw materials. One of the materials that can be used as bioethanol is empty fruit bunches of palm oil (TKKS). TKKS is a plantation waste that has not been widely used, which has a high lignocellulosic content. In this research used TKKS as raw material to produce bioethanol through process stages namely delignification, hydrolysis, fermentation, and distillation. The purpose of this research is to see the effect of sulfuric acid concentration on TKKS hydrolysis and fermentation time to bioethanol density produced. The result showed that ethanol density was obtained 0,987 gr / ml at 3 days with addition of H2SO4 3%, analysis of TKKS with FTIR obtained functional group showing the glucose content at TKKS on 950-1200 cm-1 and highest ethanol is 9% at 5-day fermentation with 3% H2SO4.